The birth of Caribbean civilisation : a century of ideas about culture and identity, nation and society - Bolland, O. Nigel (Ian Randle KingstonJM, 2004)
Shows some of the variety, commonalities, contrasts and connections in the ideas of Caribbean intellectuals in the late nineteenth century to the present day.